2021
DOI: 10.1002/jcsm.12715
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the mass and quality of the quadriceps with age and sex and their relationships with knee extension strength

Abstract: Background Although muscle quality evaluations are currently considered important for diagnosing sarcopenia, data from the general population are lacking. This study used mid‐thigh computed tomography measurements to evaluate age‐related and sex‐related differences in quadriceps femoris muscle quality and mass and their relationships with knee extension strength (KES). Methods Cross‐sectional data from 520 Japanese individuals (273 men and 247 women, mean age: 63.1 ± 10.6 years) were analysed. Mass and quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…From the 10‐mm‐thick slices, the images of the right midthigh at the centre of the end‐to‐end images were analysed to measure thigh, quadriceps, vastus lateralis, and subcutaneous CSA by SliceOmatic Ver 4.3 software (TomoVision, Magog, Canada). Moreover, manual range selection was used to measure the intermuscular adipose tissue (IMAT) of CSA in thigh, according to the procedure of Mizuno et al 16 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the 10‐mm‐thick slices, the images of the right midthigh at the centre of the end‐to‐end images were analysed to measure thigh, quadriceps, vastus lateralis, and subcutaneous CSA by SliceOmatic Ver 4.3 software (TomoVision, Magog, Canada). Moreover, manual range selection was used to measure the intermuscular adipose tissue (IMAT) of CSA in thigh, according to the procedure of Mizuno et al 16 …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, manual range selection was used to measure the intermuscular adipose tissue (IMAT) of CSA in thigh, according to the procedure of Mizuno et al . 16 …”
Section: Methodsmentioning
confidence: 99%
“…As the LLMQ used in this study was LS per unit kilogram of lower limb muscle, the relationship between LLMQ and walking speed followed the results of previous studies, 3,4 showing a correlation between lower walking speed and lower limb muscle weakness. In a previous study on lower extremity muscle quality, Mizuno et al 22 found a significant relationship between knee extensor strength and computed tomography values of the vastus medialis muscle in women (β = 0.20, P = 0.025), suggesting that dysfunction of type I fibers in the vastus medialis muscle due to fat infiltration may lead to decreased knee extensor strength. Furthermore, excessive infiltration of adipose tissue into the muscle tissue did not correlate with the size of the muscle cross-sectional area, but was associated with decreased muscle strength and physical performance.…”
Section: Discussionmentioning
confidence: 95%
“…Mizuno et al reported that, in healthy subjects, longitudinal changes in quadriceps muscles mass and CT attenuation were different between males and females. 28 Furthermore, female COPD patients have been reported to have less muscle mass, higher EI, and less PA. 8 Therefore, it is unclear whether similar results can be obtained in female subjects. Third, most of the participants had moderate‐to‐severe airflow obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Second, all participants were male. Mizuno et al reported that, in healthy subjects, longitudinal changes in quadriceps muscles mass and CT attenuation were different between males and females 28 . Furthermore, female COPD patients have been reported to have less muscle mass, higher EI, and less PA 8 .…”
Section: Discussionmentioning
confidence: 99%